Dampak Pernikahan Dini Terhadap Kehamilan Remaja Putri Suku Buton Di Desa Simi Kecamatan Waisama Kabupaten Buru Selatan - Suryanti Buton; Yusriani; Fairus Prihatin Idris (Journal of Muslim Community Health, 2021)
Background: Child marriage can cause various health problems. Based on the preliminary results, it was found that 2 informants experienced the worst impact of early marriage when the baby died at birth and at the age of 1.5 years. The purpose of this research is to obtain information, to study, and to analyze in-depth the impact of early marriage on the pregnant of young women of the Buton tribe in Simi Village, Waisama District, South Buru Regency. Methods:This research method is qualitative with a case study approach. Qualitative research was used with the intention of examining the impact of early marriage on the health of Butonese teenage girls through in-depth interviews, observation and documentation during the study. Results:The results of this study found that most of the regular informants in this study had performed the posuo ritual (pingitan) but most of the informants still felt the health impact of getting married at a young age. The 7 regular informants, most of them experienced health problems, namely the problem of pregnancy there was a decrease. fetal movement, abortion and anemia. Conclusion: The conclusion of this study is that early marriage has a negative impact on the health of young women of the Buton tribe, both adolescents who do the posuo ritual or those who do not.